American corrections: theory, research, policy, and practice - DeLisi, Matt (Jones and Bartlett Publishers, 2010)
Corrections and Its Place in the Criminal Justice System -- The Philosophy and History of Corrections -- The Law and Corrections -- Sentencing and Offender Classification -- The Pretrial Period and Jails -- Diversion Pretrial Treatment and Prevention -- Intermediate Sanctions -- Probation -- Prisoners and Inmate Behavior -- Prison Organization Management and Programs -- Parole -- Reentry -- Juvenile Corrections -- Women and Corrections -- Capital Punishment and Civil Commitment